Green Tourism: A Sustainable Tourism Marketing Approach for Tourism Services - Firmansyah; Fikri Alfatih; Radit Nugroho (Journal of Social Science and Business Studies, 2024)
Our aim was to analyze sustainable marketing strategies (green marketing) in the context of sustainable tourism, with green tourism as an intervening variable. We used an explanatory survey method with the application of the path analysis method for this research. The results of this research conclude several important findings. First, green marketing positively influences green tourism among tourist destination managers, as reflected in the influence value of 0.503. Second, green marketing strategies also have a positive effect on sustainable tourism among tourist destination managers, with an influence value of 0.426. Third, sustainable tourism among tourist destination managers is positively influenced by green tourism, with an influence value of 0.495. Finally, there is the influence of green marketing on sustainable tourism through green tourism among tourist destination managers, with an influence value of 0.248. These findings provide important insights into how sustainable marketing strategies can influence the development of environmentally friendly and sustainable tourism.